Impacts of application patterns and incorporation rates of dredged Yellow River sediment on structure and infiltration of saline-alkali soil - Li, Kesheng; Kong, Weihang; Xu, Wenshuo; Liu, Chuanxiao (International Journal of Agricultural and Biological Engineering, 2022)
Soil salinization is an issue of global concern. Despite recent evidence indicates that application of sediments into saline-alkali soil in Yellow River Delta as an additive can increase crop yield, its effects on soil structure and infiltration remain uncertain. In this study, the comprehensively analyses were conducted on the soil infiltration and microstructure of the soil treated with three sediment application layers (surface layer at 0-15 cm, lower layer at 15-30 cm, and plough layer at 0-30 cm) and four sediment incorporation rates (0, 2%, 5% and 10%), using soil column simulation experiment. Results indicated that the dredged Yellow River sediments can improve the infiltration capacity of saline-alkali soil; and the infiltration capacity increased with the rising sediment incorporation rate under the given application pattern. Compared with the control, applying dredged Yellow River sediments at 10% rate at lower layer and plough layer significantly facilitated the soil infiltration of the saline-alkali soil. Soil macro-porosity for T2, T5 and T10 was 26%, 52% and 158% more than that for the control, respectively. This phenomenon was attributed to the increased soil macro-porosity, due to the improved soil microstructure with the incorporation of sediment into the saline-alkali soil. Moreover, the cumulative infiltration was fitted better with Kostiakov infiltration model than Horton and Philip models. Keywords: saline-alkali soil, Yellow River sediment, soil infiltration, microstructure, incorporation rate, application pattern DOI: 10.25165/j.ijabe.20221504.6556 Citation: Li K S, Kong W H, Xu W S, Liu C X. Impacts of application patterns and incorporation rates of dredged Yellow River sediment on structure and infiltration of saline-alkali soil. Int J Agric & Biol Eng, 2022; 15(4): 139–146.